KAJIAN SIFAT OPTIK FILM TIPIS BST DIDADAH NIOBIUM DAN TANTALUM - Huriawati, Farida; Irzaman, Irzaman (Jurnal Pendidikan Fisika dan Keilmuan (JPFK), 2015)
In this research thin films of Barium Strontium Titanate (BST) has been synthesis with different compositions Ba0,5Sr0,5TiO3 and Ba0,25Sr0,75TiO3 which doped by Nb2O5 (Niobium) and Ta2O5 (Tantalum) on Si (100) type-p substrate. Thin films were produced by chemical solution deposition technique (CSD) and spin coating technique with annealing temperature at 850oC, 900oC dan 950oC. Rotation velocity at 3000 rpm and time of rotation is 30 seconds. Characterization of Films is optic Characterization (absorbance ana reflectance). From the Characterizations were obtained BNST thin film with 5% doping and anneling temperature at 8500C as photodiode light sensor which applied in electronic circuit.Â